Sherris medical microbiology an introduction to infectious diseases - Ryan, Kenneth J. (Kenneth James) 1940- (McGraw-Hill, Medical Pub. Division, 2018)
For more than a quarter-of-a-century, no other text has explained the link between microbiology and human disease states better than Sherris Medical Microbiology. Through a vibrant, engaging approach, this classic gives you a solid grasp of the significance of etiologic agents, the pathogenic processes, epidemiology, and the basis of therapy for infectious diseases